Gambaran Peresepan Antibiotik Golongan Fluorokuinon Pada Pasien Rawat Jalan di RUmah Sakit Ibnu Sina Gresik - shofiyah, lailatus; Nasyanka, Anindi Lupita; Na'imah, Janatun (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
One of the indicators used in assessing the success of drug use is prescription. Fluoroquinolone antibiotiks are one of the most frequently prescribed drugs. if the use is too high it will cause antibiotik resistance. The purpose of this study was to determine the overview of fluoroquinolone antibiotik prescription in outpatients at Rumah Sakit Ibnu Sina Gresik with a descriptive observational study design that carried out retrospective secondary data collection. This study used a population of all outpatient prescriptions who received fluoroquinolone class antibiotik therapy on February 1, 2020 - February 29, 2020 at the Outpatient Pharmacy Installation of Rumah Sakit Ibnu Sina Gresik with a sample size of 311 sheets of prescriptions taken by total sampling technique. It can produce the highest prescription profile from each of the analysis variables, namely 1 antibiotik item of 88.75%, lung clinic 21.87%, capsule preparation 58.80%, over 55 years of age 47.91%, generik fluoroquinolones 81.67% BPJS patients were 67.52% and fluoroquinolone second generation 69.77%. These results can be seen from the overview of outpatient prescriptions at Rumah Sakit Ibnu Sina Gresik on February 1 - February 29, 2020. Keywords: Prescribing, Antibiotik, Fluoroquinolone